Flaws in the Authenticated Lesson Plans in the Department of Literature and Languages through the Lens of Trainee Teachers in Zambian Secondary Schools - Pethias Siame (PT ARRUS Intelektual Indonesia, 2023)
The paper presents common flaws in the lesson plans which were authenticated by Heads of Department (HoDs) in the Department of Literature and Languages across Zambia for student teachers from Kwame Nkrumah University who underwent their teaching experience in 2020 and 2022. A flaw is synonymous to defect, fault and pitfall which should be viewed as a challenge or problem which requires immediate attention and possible solutions. Teaching experience allows trainee teachers to apply theoretical knowledge and skills gained during their course of training. The study employed Critical Discourse Analysis framing to account for flaws in the authenticated lesson plans. Qualitative approach, observation and document analysis methods were adopted. Thematic and descriptive concepts were used to analyse the data. The study shows that some mentors of students on teaching experience did not guide the trainee teachers well. In addition, some HoDs did not take keen interest to check the nature of lesson plans before authenticating them. Lesson plans lacked brainstorming during introductions, had disoriented developments which lacked class and individual activities. It is recommended that HoDs conduct thorough discourse analysis of what they authenticate.